Reliable and Swift Message Broadcast Method in Vehicular Ad Hoc Networks - Jaesung Park; Yujin Lim (International Journal of Distributed Sensor Networks)
A vehicular ad hoc network (VANET) could deliver safety-related messages reliably within a short time to increase road safety. Since safety-related messages should be sent to a set of unspecified receivers, they are delivered by broadcast method. However, the broadcast method specified in the IEEE 802.11p does not have a collision avoidance procedure and receivers do not acknowledge when they receive a broadcast frame. In addition, frames could be lost and corrupted. Therefore, as the portion of nodes that do not receive a broadcast frame increases, the effectiveness of a safety application decreases. To tackle the problem, we propose a reliable and swift message broadcast method (RSMB). In RSMB, to expedite message dissemination process, a relay node is selected in a distributed manner considering the progress made to a frame and the delay requirements of an application. In addition, a relay node broadcasts a message multiple times to assure that the probability that the other nodes successfully receive the message at least once is larger than a given threshold value. Since the number of rebroadcasts is regulated based on the successful message reception probability, the additional bandwidth needed to increase the reliability of broadcast is reasonably small.